Social Order in a Fragile State: Rio's Favelas. (October 2016) - Rodet, Cortney S.
Abstract: A peculiar social order exists in the favelas of Rio de Janeiro, where the drug factions that control them permit humanitarian activity which curbs drug use and faction affiliation. This article provides an institutional perspective on faction control of the favelas where a lack of government presence fosters faction legitimacy among residents. Allowing humanitarian organisations to operate in the favelas creates common knowledge among residents within a large coordination game where factions signal a desire to cooperate. Legitimisation among residents improves faction profits, while residents benefit from 'law and order', public services and public goods that are not provided by the state.